PENGARUH MIKROBA TANAH TERHADAP PERTUMBUHAN DAN HASIL PANEN KEDELAI (Glycine max L.) - Purwaningsih, Sri (BERITA BIOLOGI, 2001)
A study was conducted in order to know the effect of soil microorganism as biofertilizer on the growth and yield of soybean (Glycine max L.) in Malang, East Java.The purpose of the study was to get inoculants as biofertilizer to improve the production of soybean.The experiment was carried out in Bantur village, Bantur district, South Malang, East Java, by using the rice land.The strain used were five single inoculants as follows: A (Bio 20R + Bio 22R + Bio 277R), B (Bio 277R + Bio 278R + Bio 302R), C (1L + 8L + Bio 302R), D (Bio 20R + Bio 22R + Bio 277R + Bio 278R + Bio 302R + 1L + 8L), V (MVA fungi), and four mixed inoculants (AV, BV, CV, and DV). Four controls as uninoculated plant and without fertilizer (Ki), uninoculated plant and with Urea fertilizer equal to 100 kg/ha (K2), uninoculated plant and with TSP fertilizer equal to 80 kg/ha (K3), uninoculated plant and with Urea and TSP fertilizer (K4). The experiment was designed as Randomized Complete Block as 13 treatments with three replications for each treatment, and interval planted with 20 x 35 cm. The plants were harvested after 90 days. The parameters of investigation were the dry weight of canopy, roots, root nodules, seeds, 100 of seeds, number of nodules and pods with harvest productions. The results showed that single inoculants (MVA fungi) and mixed inoculants CV (1L + 8L + Bio 302R) and MVA fungi) gave better results on the production of soybean.